Cultural Terms on Two Translated Versions of Soethama’s Short Stories: A Comparative Study - Pratica Wijaya, Lina; Mas Indrawati, Ni Luh Ketut (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 27 No 1 (2020): MaretDO - 10.24843/ling.2020.v27.i01.p04, 2020)
Translating a literary work from different culture, some problems will emerge, especially related to culture-specific terms since two different languages are certainly have two different cultures. We have to understand that literary work is not just a common writing work, but also contains culture, tradition and people’s daily life especially in ecology and material culture (artefacts). There are three problems in this study: 1) cultural terms related to ecology and material culture (artefacts) in the short story; 2) semantic features of the cultural terms; and 3) translation strategies applied by two translators when translating the cultural terms of the same short story by Gde Aryantha Soethama entitled Seekor Ayam Panggang which is translated by two different translators; Jeanette Lingard and Vern Cork. The theories applied in this study were theories of cultural aspects (Newmark, 1988:95), theories of semantic features as proposed by Larson (1984) and Yule (1985/2010), and theory of translation strategies by Pedersen (2005) of Extralinguistic Culture-bound References. The collected data were analyzed comparatively. From the discussion of eight cultural terms related to ecology and material culture (artefacts) and their sixteen translations, it is discovered that some of the features were not carried out by the translations. Considering these two languages have different culture, it is inevitable to miss some components in the semantic features and the decision of using more target language-oriented strategies is part of the way to bridge the differences between culture.